Data from: Population connectivity and genetic structure of burbot (Lota lota) populations in the Wind River Basin, Wyoming - Underwood, Zachary E.; Mandeville, Elizabeth G.; Walters, Annika W. (Dryad Digital Repository, 2020)
Burbot (Lota lota) occur in the Wind River Basin in central Wyoming, USA, at the southwestern extreme of the species’ native range in North America. The most stable and successful of these populations occur in six glacially carved mountain lakes on three different tributary streams and one large main stem impoundment (Boysen Reservoir) downstream from the tributary populations. Burbot are rarely found in connecting streams and rivers, which are relatively small and high gradient, with a variety of potential barriers to upstream movement of fish. We used high-throughput genomic sequence data for 11,197 SNPs to characterize the genetic diversity, population structure, and connectivity among burbot populations on the Wind River system. Fish from Boysen Reservoir and lower basin tributary populations were genetically differentiated from those in the upper basin tributary populations. In addition, fish within the same tributary streams fell within the same genetic clusters, suggesting there is movement of fish between lakes on the same tributaries but that populations within each tributary system are isolated and genetically distinct from other populations. Observed genetic differentiation corresponded to natural and anthropogenic barriers, highlighting the importance of barriers to fish population connectivity and gene flow in human-altered linked lake-stream habitats. VCF fileThis is a .vcf file produced by calling variant genetic sites using samtools and bcftools. For each variant site identified, we required that >60% of all individuals had 1 or more read at that locus.variants_0.6.vcfentropy_variants0.6Input file for analysis with the "entropy" model. This file is a filtered version of the VCF file, including genotype likelihoods for loci with MAF>1%. Additionally, we randomly selected 1 SNP per contig for contigs with multiple variant sites, to ensure independence of SNPs.split_scaffold_burbot_ref_long_94Because there are no existing genomic resources for burbot, we constructed an artificial reference ...